Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

a+b – (a - (a - a)); use a = = -5, and b = -6


Sagot :

Answer:

 a + b - ( a - ( a-a)) = - 6

Step-by-step explanation:

Explanation:-

Given that a =-5 and b=-6

Given expression

        a + b - ( a - ( a-a))

  =  -5 +(-6)) - ( -5 -(-5-(-5))

  = -5 -6 - (-5 -0)

 =  - 5 - 6 +5

= - 6

Final answer:-

 a + b - ( a - ( a-a)) = - 6